Compounding and rheometry of PLA nanocomposites with coated and uncoated hydroxyapatite nanoplatelets - Tomczynska, Magdalena M.; Choong, Gabriel Y.H.; De Focatiis, Davide S.A.; Grant, David M.; Parsons, Andrew J. (2016)
Polylactic acid and novel nanoplatelets of hydroxyapatite (HANP) were compounded in a laboratory scale twin-screw extruder and injection moulded to shape. The effect of HANP loading content, between 1 wt% and 10 wt%, and of HANP surface coating with tailored molecular dispersants, on the processability and rheological behaviour were investigated. Dispersion of HANP within the matrix system was determined qualitatively using transmission electron micrographs. Surface coating of HANP with dispersants was observed to change the state of HANP dispersion in the nanocomposites. This was also reflected in the changes of the nanocomposites’ rheological response with the moduli of coated HANP systems increasing at lower frequencies.